2007
DOI: 10.1002/pits.20257
|View full text |Cite
|
Sign up to set email alerts
|

Interventions addressing transition difficulties for individuals with autism

Abstract: Transitioning between activities can pose difficulties when working with students with autism. Individuals with autism may resist transitions by exhibiting a host of problem behaviors such as aggression and tantrums. Although scant, there is available research that provides sound recommendations for assessing and intervening for problem behaviors occurring during transition times. The present article presents a summary of the current transition literature, with a special emphasis on interventions for students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 22 publications
0
47
0
2
Order By: Relevance
“…Although advance notice procedures are widely considered to be effective (e.g., Banda and Grimmett 2008;Lequia et al 2012;Koyama and Wang 2011;Sterling-Turner and Jordan 2007), discrepant findings regarding the effectiveness of advance notice have been reported (Cote et al 2005;McCord et al 2001;Wilder et al 2006;Waters et al 2009;Wilder et al 2010;Wilder et al 2007). Some researchers have speculated that these negative results indicate that advance notice procedures are ineffective (Wilder et al 2010).…”
Section: Advance Noticementioning
confidence: 97%
See 2 more Smart Citations
“…Although advance notice procedures are widely considered to be effective (e.g., Banda and Grimmett 2008;Lequia et al 2012;Koyama and Wang 2011;Sterling-Turner and Jordan 2007), discrepant findings regarding the effectiveness of advance notice have been reported (Cote et al 2005;McCord et al 2001;Wilder et al 2006;Waters et al 2009;Wilder et al 2010;Wilder et al 2007). Some researchers have speculated that these negative results indicate that advance notice procedures are ineffective (Wilder et al 2010).…”
Section: Advance Noticementioning
confidence: 97%
“…Sterling-Turner and Jordan (2007) found that, for individuals with autism, photographic cues, activity schedules, and video priming strategies were all effective at reducing transition-related problem behavior. Banda and Grimmett (2008) conducted a systematic review of the autism literature and reported activity schedules were effective at reducing transition-related problem behavior; Koyama and Wang (2011) reported similar results with individuals with other intellectual disabilities.…”
Section: Positive Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…These strategies include minimizing wait time, teaching class-wide transition rules, and providing warnings prior to transitions (Sterling-Turner and Jordan 2007). When class-wide procedures fail to increase the independent performance of students with developmental disabilities, concurrent individualized behavioral interventions may be necessary to support the student.…”
mentioning
confidence: 99%
“…During a typical school day, most pre-school and elementary students engage in multiple transitions between activities (Sterling-Turner and Jordan 2007). As students may spend an average of 25 % of their day engaged in transition, their ability to quickly move between activities is considered an important behavior for school success (Sainato et al 1987;Schmit et al 2000).…”
mentioning
confidence: 99%